The role of mentoring in the formation of personal and professional qualities of the future officers of the Highly mobile airborne troops - Георгієв, Василь (Pedagogy of Higher and Secondary Education, 2014)
Georgiev V. M. The role of mentoring in the formation of personal and professional qualities of the future officers of the Highly mobile airborne troops. This article analyzes the problem of pedagogical mentoring in modern education. The main purpose of mentoring in the military schools, as the author considers, is the formation of cadets’ positive emotional attitude towards their future profession. The main principles of mentoring activities are: voluntary and purposefulness; respect for the cadet’s personality; benevolence; own example; and orientation of planned activities on education and professional development of the future airborne officers.